Efficacy and Safety of Topical Therapy With Botanical Products for Melasma: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wang, Tianyun; Wang, Youmei; Wang, Jue; Chen, Hongwei; Qu, Biao; Li, Zheng (Frontiers in Medicine, 2022)
Botanical products have been increasingly popular in topical therapies for melasma, as presumed safer and milder than fully synthetic products. Although the efficacy of different topical botanicals has recently been substantiated through randomized controlled trials (RCTs), there is a lack of sufficiently pooled evidence on their efficacy and safety for the treatment of melasma. Herein, a systematic review and meta-analysis was conducted on the efficacy and safety of topical botanical products for the treatment of melasma, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). All RCTs on the use of topical botanical products for the treatment of melasma in humans were included, except for trials enrolling pregnant patients. The primary outcome was Melasma Area and Severity Index (MASI) or its variation. The secondary outcomes included Mexameter® reading, melasma improvement evaluated by participants, and any reported adverse events (AEs). As a result, twelve eligible trials comprising 695 patients with melasma from 6 different countries were included. The topical botanical products contained active ingredients which varied among trials as follows: herb-derived molecule, extracts of a single herb, and extracts of compound herbs. Topical therapy with botanical products significantly improved melasma with a large effect on MASI reduction (SMD −0.79, 95% CI −1.14 to −0.44, p < 0.00001), and a moderate effect on Mexameter® reading reduction (SMD −0.52, 95% CI −0.81 to 0.23, p = 0.0005), when compared with placebo. It also showed a similar improvement of melasma with a better safety profile (RR 0.37, 95% CI 0.15–0.88, p = 0.02), when compared with active-comparators. Botanical products were well-tolerated across studies, with no serious AEs reported. Despite the limitations such as small sample size, short duration of follow up and varied botanical products, this work still represents the best level of evidence currently available on topical use of botanical products on melasma. Moreover, it should be noted that more well-designed studies are needed before recommending topical botanical products as a viable treatment option for melasma. Systematic Review Registration PROSPERO, identifier: CRD42021256328.